Optimalisasi Mal Pelayanan Publik dalam Meningkatkan Kualitas Pelayanan di Kabupaten Sumenep (Studi Kasus Dinas Penanaman Modal, Pelayanan Terpadu Satu Pintu, Dinas Kependudukan dan Pencatatan Sipil dan Dinas Kesehatan Kabupaten Sumenep) - Sabib Nurullah; Agus Prastyawan; Pardamean Daulay (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the role of Public Service Malls in improving the quality of services in Sumenep Regency. The research method uses a qualitative descriptive approach. The results of the study show that the Public Service Mall of Sumenep Regency with Mall officers must appear neat and polite, including the attitude of the service provider, 2. Providing services at the Public Service Mall of Sumenep Regency, the officers are very reliable in doing various things, in this Mall, accuracy and speed are needed in working. 3. The responsiveness of the administrative service providers at the Public Service Mall of Sumenep Regency is very high and good, in providing services by quickly responding to public desires. 4. Guarantees from the officers of the Public Service Mall of Sumenep Regency for their work shown to the applicant, with high work discipline and permits received to be re-checked. 5. Officers at the Public Service Mall of Sumenep Regency are very sympathetic to the public, this can be seen by providing convenience and assistance to the applicant. The conclusion of this study shows that the optimization of public services is very good, this can be seen from the dimensions of the quality of public services provided to the public. Public service officers at Sumenep Mall have shown responsiveness to customer demands for fast and efficient solutions to individual problems. Keywords: Optimization, Public Service and Service Quality